PELAKSANAAN UNDANG-UNDANG NO. 16 TAHUN 2019 DI KANTOR URUSAN AGAMA (KUA) KECAMATAN NOGOSARI KABUPATEN BOYOLALI - Lailatul Faizah, Arfina; Syamsuddin; Baehaqi (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM IBLAM), 2023)
Implementation of Law no. 16 of 2019 at the Office of Religious Affairs (KUA) of Nogosari District, Boyolali Regency. Thesis. Ahwal Al Syakhsyiyah Study Program, Faculty of Sharia and Islamic Economics, Mamba`ul Ulum Islamic Institute, Surakarta.This study aims 1) To find out how the implementation of Law no. 16 of 2019 Article 7 at the Nogosari KUA, 2) Supporting and inhibiting factors in the implementation of Law Number 16 of 2019 Article 7 at the Religious Affairs Office of Nogosari District.The approach taken in this study is a qualitative approach, a type of normative empirical research or field research. This means that the data comes from interviews, observations, personal documents and other official documents. Data analysis technique used is data collection is data collection, data reduction, data presentation and drawing conclusions. Data validity assurance techniques are carried out by checking trust, transferability and dependency checks.The results of this study found that the application of the age limit for marriage according to Law no. 16 of 2019 at the KUA in Nogosari District, it has been effective with a decrease in the number of early marriages every year. In its application there are inhibiting factors, namely: 1) level of education; 2) lack of legal awareness; 3) uncontrolled association; and 4) the decision on the PA's marriage dispensation. The supporting factors are: 1) the level of community education; 2) socialization; 3) public awareness